2014
DOI: 10.1249/mss.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

Earbud-Based Sensor for the Assessment of Energy Expenditure, HR, and V˙O2max

Abstract: Introduction/Purpose The goal of this program was to determine the feasibility of a novel noninvasive, highly miniaturized optomechanical earbud sensor for accurately estimating total energy expenditure (TEE) and maximum oxygen consumption (VO2max). The optomechanical sensor module, small enough to fit inside commercial audio earbuds, was previously developed to provide a seamless way to measure blood flow information during daily life activities. The sensor module was configured to continuously measure physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…[17] However, there is a dearth of evidence in support of this approach to quantifying energy expenditure during exercise, specifically when measured within the ear. Leboeuf et al [10] had participants perform a graded maximal exercise treadmill test, comparing heart rate and caloric expenditure to ECG and indirect calorimetry, respectively. Both variables derived from the earbud sensors were highly correlated (heart rate R 2 ¼ 0.98 kcal, R 2 ¼ 0.86 kcal) with the criterion measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17] However, there is a dearth of evidence in support of this approach to quantifying energy expenditure during exercise, specifically when measured within the ear. Leboeuf et al [10] had participants perform a graded maximal exercise treadmill test, comparing heart rate and caloric expenditure to ECG and indirect calorimetry, respectively. Both variables derived from the earbud sensors were highly correlated (heart rate R 2 ¼ 0.98 kcal, R 2 ¼ 0.86 kcal) with the criterion measures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown this technology to be accurate for measuring heart rate and energy expenditure. [10] This can be used to monitor exercise intensity in real time while providing auditory feedback through the earbuds, or provide summative information regarding average heart rate, distance travelled and calories expended at the conclusion of exercise periods.…”
Section: Fitbit Charge Activity Trackermentioning
confidence: 99%
See 1 more Smart Citation
“…While hearables have a number of affordances for ubiquitous computing, many of these affordances are particularly relevant for affective computing, in which computers have the ability "to recognize, express, and "have" emotions" [9]. Hearables are particularly useful for recording affective data input, as the ear is a rich source for collecting many types of biological signals pertaining to our emotional states; ear-mounted sensors can potentially monitor cardiovascular, respiratory, perspiration, and brain states [10,11]. This type of data has been utilized in a variety of different applications, including fitness tracking, health monitoring, improved computer interfaces, and various context-aware/"smart" systems.…”
Section: From Headphones To Hearablesmentioning
confidence: 99%
“…Reflective photoplethsmography (PPG) sensors have appeared in a number of different wearable devices, including various health trackers, smartwatches, and hearables [10,28,29], allowing a relatively inexpensive and non-invasive method for obtaining data pertaining to the user's heart rate and heart rate variability. The underlying technology for obtaining this type of heart rate and other blood related activity is remarkably simple, and therefore some wearable devices on the market even contain multiple PPG sensors for redundancy.…”
Section: Photoplethsmography (Ppg)mentioning
confidence: 99%